A pioneering experience in Brazil: the creation of a center for assistance and research for medical residents (NAPREME) at the Escola Paulista de Medicina, Federal University of São Paulo - Nogueira-Martins, Luiz Antonio; Stella, Regina Celes de Rosa; Nogueira, Helio Egydio (São Paulo Medical Journal, 1997)
The decision to develop a treatment service for medical residents at Escola Paulista de Medicina was influenced by three main factors: the suicide of four young doctors (2 residents) at this institution between 1995 and 1996, a research study that investigated stress among medical residents and the experience of other countries in response to similar problems. NAPREME has the following objectives: to help to reduce stress among residents, stimulate professional and personal development, prevent professional dysfunction and emotional disorders, offer psychological treatment, assess the tutors of residency programmes and develop research programmes to better identify risk factors for emotional problems during the residency period. We hope that by doing this the overall quality of the residency programme will improve, both for the professionals and the patients.